2010
DOI: 10.1159/000285506
|View full text |Cite
|
Sign up to set email alerts
|

Extended Monitoring of the Sedated Patient: Bispectral Index, Narcotrend® and Automated Responsiveness Monitor

Abstract: It has been demonstrated that a processed EEG derivative may reflect the patient’s level of consciousness during endoscopic sedation. However, to date a clinical benefit of EEG monitoring with respect to relevant safety parameters in routine gastrointestinal endoscopy has not been demonstrated. During long-lasting procedures (e.g. ERCP, ESD) a propofol-sparing effect has been shown, but a benefit regarding patient safety could not be documented. The use of an automated responsiveness monitor may help to achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Sedation and analgesia represent a continuum ranging from minimal (anxiolysis) or moderate to deep sedation and general anesthesia 16 17 24 25 29 . Moderate sedation is recommended as it provides adequate anxiolysis, pain control, and amnesia, being safer than deep sedation 25 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Sedation and analgesia represent a continuum ranging from minimal (anxiolysis) or moderate to deep sedation and general anesthesia 16 17 24 25 29 . Moderate sedation is recommended as it provides adequate anxiolysis, pain control, and amnesia, being safer than deep sedation 25 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Capnometry has also been reported to be useful for preventing oversedation during ESD [23]. The concurrent use of BIS index assessment and capnometry might allow close monitoring of patients [24]. The types and dosages of concurrently used analgesics remain largely uninvestigated.…”
Section: Safety Parameters During Recoverymentioning
confidence: 99%
“…Most of the many other studies [432][433][434][435][436][437][438][439][440][441], however, showed no significant reduction in the required propofol dose in mostly interventional endoscopies. The use of BIS monitoring also did not lead to a reduction in surrogate patient safety parameters (hypoxemia and RR drop) [436].…”
Section: Evidence Level 1b Strong Consensusmentioning
confidence: 92%